Budgeting in Moldova - Kraan, Dirk-Jan (OECD Publishing, 2010)
The institutional features of the budget process in Moldova are in a permanent flux, because of ambitious reform programmes that have been adopted in recent years and that are planned for the future. This article examines the Moldovan budget formulation process, the role of parliament, budget execution and budget discipline, the supply side of the budget process (public administration and service delivery), and accounting and audit. JEL classification: H610